2023
DOI: 10.3389/fragi.2023.1272118
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender affect immune aging

Anna Calabrò,
Giulia Accardi,
Anna Aiello
et al.

Abstract: The proposed review aims to elucidate the intricate interplay between biological factors (sex differences) and socially constructed factors (gender differences) in the context of immune aging. While the influence of biological differences between men and women on various aspects of immune responses has long been recognized, it is crucial to acknowledge that gender, encompassing the social and cultural roles and expectations associated with being male or female, also significantly shapes these processes. Gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Coming back to COVID-19 older people mortality, there are conflicting findings in the literature [ 7 ]. However, this quoted review revealed the following: (a) Consistent with evidence indicating that women tend to outlive men even during severe famines and epidemics, women exhibit greater resilience [ 8 ], although conflicting data exist regarding female centenarians in Northern Italy [ 9 ]; (b) Due to their frailty [ 10 ], centenarians, on the whole, generally succumb to COVID-19 at rates similar to or greater than other older individuals [ 11 13 ], with the exception of Japan, where their numbers continued to rise due to general precautions against viral infections, such as social distancing [ 14 ]; (c) During the initial wave of the pandemic in 2020, before introduction of vaccines, “older” centenarians (> 101 years old) exhibited greater resilience to COVID-19 than “younger” ones (< 102 years old) [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Coming back to COVID-19 older people mortality, there are conflicting findings in the literature [ 7 ]. However, this quoted review revealed the following: (a) Consistent with evidence indicating that women tend to outlive men even during severe famines and epidemics, women exhibit greater resilience [ 8 ], although conflicting data exist regarding female centenarians in Northern Italy [ 9 ]; (b) Due to their frailty [ 10 ], centenarians, on the whole, generally succumb to COVID-19 at rates similar to or greater than other older individuals [ 11 13 ], with the exception of Japan, where their numbers continued to rise due to general precautions against viral infections, such as social distancing [ 14 ]; (c) During the initial wave of the pandemic in 2020, before introduction of vaccines, “older” centenarians (> 101 years old) exhibited greater resilience to COVID-19 than “younger” ones (< 102 years old) [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, the disease is more severe and lethal in men than in women [ 3 , 7 ]. The degree of immune-inflammatory responses differs between men and women and persists throughout life [ 7 , 8 , 45 ]. Besides sex hormones, sex chromosomes play a role, as several immune genes are found on the X chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize this limitation, we only reported results that survived multiple comparisons, showed effect sizes above the minimum established, and were further supported by Bayesian evidence. Moreover, the study sample has twice more females than males, which may impact results given the unquestionable role of gender in the development and outcomes of immune responses [ 64 , 65 ]. Indeed, 80% of autoimmune diseases occur in women, who typically show stronger immune responses than males.…”
Section: Discussionmentioning
confidence: 99%
“…Sex and age are two key factors that have been linked to the development of reactive antibodies in certain autoimmune diseases. Many autoimmune conditions like SLE, SjS, and type 1 diabetes exhibit a higher prevalence in females compared to males [26][27][28][29]. On the contrary, it has been observed that men with SLE more frequently suffer from renal impairments such as LN and face a heightened risk of progressing to end-stage renal disease, although there is some uncertainty surrounding this question [27,30,31].…”
Section: Introductionmentioning
confidence: 99%